Participatory governance in China: analysing state-society relations in participatory initiatives in Suzhou. Issue 3 (June 2019) - Chang, Ying; Lau, Mandy; Calogero, Pietro
Abstract : Participatory governance has been increasingly promoted in China since 2006. Whilst the state appears to be supportive of nurturing self-governance at the community level through providing financial incentives, it is worth investigating whether the state hampers citizen autonomy in practice. This article examines the implementation of participatory initiatives in a middle-class neighbourhood within the China-Singapore Suzhou Industrial Park (SIP). Through interviews and observing the interactions between state actors, residents and non-governmental organisations (NGOs), this paper examines the impact of changing the facilitator of self-governance initiatives from academics to NGOs. The findings reveal complex relations: although the state does not interfere in participatory processes directly, state-defined evaluation criteria that privilege 'innovative' practices, and budget constraints of NGOs, have weakened the capacity of residents to practise self-governance. The findings add to the literature on participatory governance by highlighting the unique role of community leaders in shaping the quality of citizen involvement in participatory initiatives in China.